Application of Flipped Classroom Model Assisted Edmodo to Improve Students' Understanding of Concepts in the Material Sound Waves - Safriana, Safriana; Rose, Junika; Ginting, Fajrul Wahdi (Universitas Syiah Kuala, 2023)
The Edmodo-assisted classroom flipped classroom model is a learning process by applying the flipped classroom model with the help of Edmodo to deliver learning materials. This study aims to determine the improvement of students' understanding of concepts in sound wave material. The type of research used is pre-experimental design. The design of this study used the Nonequivalent Control Group Design. The sampling technique that the researchers chose was purposive sampling of 40 students consisting of 20 students experimental class and control class. The research instruments used are observation sheets and student concept comprehension tests. The data analysis techniques used are learning implementation analysis, calculating the value of students' concept understanding results and N-gain score. The average N-Gain score for the control class was 0.69 with a moderate category. While the average N-Gain score for the experimental class is 0.77, which is included in the high category. So, it can be known that there is an increase in the understanding of students' concepts in the experimental class who apply the Edmodo-assisted flipped classroom model to sound wave material. This increased understanding of the concept occurred because the experimental class implemented an Edmodo-assisted flipped classroom model. In the flipped classroom model, students first learn to understand the learning materials uploaded by the teacher through Edmodo. Learning materials in the form of videos can be played repeatedly through Edmodo, so that students can learn anywhere and anytime without any time limit according to their respective learning.